2014
DOI: 10.1074/jbc.m114.609164
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evolution in the Assembly of Polyubiquitin Degradation Signals by the Shigella flexneri IpaH9.8 Ligase

Abstract: Background: IpaH bacterial ubiquitin ligases show no homology with eukaryotic ligases, and their mechanism is speculative. Results: IpaH9.8 functions as a cooperative allosteric dimer with two Ubc5ϳubiquitin binding sites per subunit. Conclusion: Kinetic parallels between IpaH and eukaryotic HECT ligases suggest convergent catalytic cycle evolution. Significance: These are the first mechanistic details of the IpaH enzyme catalytic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 52 publications
6
35
0
Order By: Relevance
“…This suggests that at least a portion of helix 7 interacts with the CSD and these contacts aid in the stability and solubility of this subdomain. Purified NSD (residues 403-516) and CSD (residues 489 -700) constructs yield dispersed 1 H, 15 N TROSY NMR spectra (Fig. 2, A and B).…”
Section: Ssph/ipah E3 Domains Can Be Divided Into Two Distinct Subdommentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that at least a portion of helix 7 interacts with the CSD and these contacts aid in the stability and solubility of this subdomain. Purified NSD (residues 403-516) and CSD (residues 489 -700) constructs yield dispersed 1 H, 15 N TROSY NMR spectra (Fig. 2, A and B).…”
Section: Ssph/ipah E3 Domains Can Be Divided Into Two Distinct Subdommentioning
confidence: 99%
“…A previous study suggested that SspH/IpaH constructs containing both LRR and E3 domains form dimers in solution (15). Such high-molecular weight complexes could negatively impact NMR-based experiments and complicate data analysis.…”
Section: Ssph1 Lrr-e3 Is Monomericmentioning
confidence: 99%
See 2 more Smart Citations
“…S1B in Supporting Information). k cat represents the number of times each enzyme site converts the substrate to the end product per unit time, whereas K m represents the E2 concentration needed to achieve a half-maximum elevation velocity for medi- ating ubiquitination (Edwards et al 2014). UBCH5A exhibited the highest IpaH4.5 activity relative to the other E2s ( Fig.…”
Section: Measuring Bacterial E3 Ligase Activity With the Micy/mko Frementioning
confidence: 99%